Hyaluronic acid-enriched bilosomes: an approach to enhance ocular delivery of agomelatine via D-optimal design: formulation, in vitro characterization, and in vivo pharmacodynamic evaluation in rabbits - Asmaa Ashraf Nemr; Galal Mohamed El-Mahrouk; Hany Abdo Badie (Taylor & Francis Group, 2022)
Agomelatine (AGO) is a dual-functional drug. It uses as an antidepressant when orally administrated and antiglaucomic when topically applied to the eye. This study aimed to formulate AGO into bilosomal vesicles for glaucoma treatment, as modern studies pointed out the effect of topical AGO on intraocular pressure for the treatment of glaucoma. A modified ethanol injection technique was used for the fabrication of AGO bilosomes according to a D-optimal design. Phosphatidylcholine (PC) to edge activator (EA) ratio, Hyaluronic acid percentage (HA%), and EA type were utilized as independent variables. The measured responses were percent entrapment efficiency (EE%), particle size (PS), polydispersity index, zeta potential, percentage of drug released after 2 h (Q2h%), and 24 h (Q24h%). The optimal bilosomal formula (OB), with the desirability of 0.814 and the composition of 2:1 PC: EA ratio, 0.26% w/v HA and sodium cholate as EA, was subjected to further in vitro characterizations and in vivo evaluation studies. The OB formula had EE% of 81.81 ± 0.23%, PS of 432.45 ± 0.85 nm, Q2h% of 42.65 ± 0.52%, and Q24h% of 75.14 ± 0.39%. It demonstrated a higher elasticity than their corresponding niosomes with a typical spherical shape of niosomes by using transmission electron microscope. It exhibited acceptable stability over three months. pH and Refractive index measurements together with the histopathological study ensured that the OB formula is safe for the eye and causes no ocular irritation or blurred vision. The OB formula showed superiority in the in vivo pharmacodynamics parameters over the AGO solution, so AGO-loaded bilosome could improve ocular delivery and the bioavailability of agomelatine.